THE IMPROVEMENT OF GROSS MOTOR DEVELOPMENT ON PRE-SCHOOL THROUGH PLAYING THROW AND CATCH BALL - Sari, Etika Purnama; Izzah, Okta Nurul (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Early childhood gross motor skills should have been able to perform activities such as jumping both one foot and two feet, catching balls, and exercising. Some children have good gross motor, but on the other hand there are children who have obstacles in the development of gross motor, so it is slower than other children. Objective: This study aims to analyze the Influence of playing throw and catch ball on gross Motor of Pre-School Age Children in Garuda Kindergarten. Method: This research design uses pre-experimental with a one-group pre-post test design approach. The population in this study was all grade A students of Garuda Surabaya Kindergarten which numbered 35 students and the sample number were 35 students. The sampling technique in this study is Total Sampling. The independent variable in the study playing throw and catch ball and the dependent variable is a gross motor development. Instruments used are observation sheets and SOP. Data analysis using Wilcoxon signed rank test. Result: The results showed that there was an increasing in children's motor development in Garuda Kindergarten The results of statistical tests showed the p value (0.000) < ɑ (0.05). Conclusion: There is an influence of playing throw and catch ball to the gross motor development of preschool-age children, this is because playing the ball will stimulate nerves and increase movement in the child so that the gross motor becomes better. To improve the development of gross Motor in children can playing throw and catch ball at home and at school.